The Impact of Government Support on Firm R&D Investments : A Meta-Analysis - Correa, Paulo; Andrés, Luis; Borja-Vega, Christian (World Bank, Washington, DC, 2013)
This paper applies meta-analysis techniques to a sample of 37 studies published during 2004-2011. These papers assess the impact of direct subsidies on business research and development. The results show that the effect of public investment on research and development is predominantly positive and significant. Furthermore, public funds do not crowd out but incentivize firms to revert funds into research and development. The coefficient of additionality impacts on research and development ranges from 0.166 to 0.252, with reasonable confidence intervals at the 95 percent level. The results are highly sensitive to the method used. The high heterogeneity of precision is explained by the wide variety of methodologies used to estimate the impacts and paper characteristics.